Learning Agility on Multigenerational Employees - Ariani, Gusti Meinar Girda; Syahrani, Syahrani; Sunarya, Herni (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
In an increasingly dynamic work environment, the ability to learn and adapt quickly, known as learning agility, has become essential. This study aims to explore the differences in learning agility among employees from the Baby Boomers, X, Y (Millennials), and Z generations. Using a library research approach, this study collects and analyzes relevant literature to identify the unique characteristics of each generation in the context of learning agility. The results indicate that each generation has different approaches and preferences toward learning and adaptation. Baby Boomers tend to be more comfortable with formal learning and direct experience, while Generation X demonstrates flexibility and the ability to learn independently. Millennials excel in technological adaptability and prefer interactive learning, whereas Generation Z favors collaborative and project-based learning. These findings highlight the importance for organizations to tailor their employee development strategies to meet the needs and preferences of each generation. By adopting a customized approach, organizations can enhance the effectiveness of learning and development, as well as improve employee performance and job satisfaction. Further research is needed to develop effective implementation strategies in a multigenerational work environment.